Li2O:Li–Mn–O Disordered Rock‐Salt Nanocomposites as Cathode Prelithiation Additives for High‐Energy Density Li‐Ion Batteries. Issue 7 (12th January 2020) - Diaz‐Lopez, Maria; Chater, Philip A.; Bordet, Pierre; Freire, Melanie; Jordy, Christian; Lebedev, Oleg I.; Pralong, Valerie
Abstract: The irreversible loss of lithium from the cathode material during the first cycles of rechargeable Li‐ion batteries notably reduces the overall cell capacity. Here, a new family of sacrificial cathode additives based on Li2 O:Li2/3 Mn1/3 O5/6 composites synthesized by mechanochemical alloying is reported. These nanocomposites display record (but irreversible) capacities within the Li–Mn–O systems studied, of up to 1157 mAh g −1, which represents an increase of over 300% of the originally reported capacity in Li2/3 Mn1/3 O5/6 disordered rock salts. Such a high irreversible capacity is achieved by the reaction between Li2 O and Li2/3 Mn1/3 O5/6 during the first charge, where electrochemically active Li2 O acts as a Li + donor. A 13% increase of the LiFePO4 and LiCoO2 first charge gravimetric capacities is demonstrated by the addition of only 2 wt% of the nanosized composite in the cathode mixture. This result shows the great potential of these newly discovered sacrificial additives to counteract initial losses of Li + ions and improve battery performance. Abstract : A new family of sacrificial cathode additives based on Li2 O:Li2/3 Mn1/3 O5/6 nanocomposites is reported with record first charge capacities of up to 1157 mAh g −1 achieved by the electrochemically activation of Li2 O. With such a high prelithiation efficacy, the first charge capacity of LiFePO4 and LiCoO2 cathodes is improved by 13% with the addition of only 2 wt% of Li2 O:Li2/3 Mn1/3 O5/6 nanocomposites.